Cell cycle-related Kinase links androgen receptor & β-catenin signaling in HCC: Why men are at a loss? - Awuah, Prince K. (2012)
Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide. It is more prevalent in men than women. Related to this, recent genetic studies have revealed a causal role for androgen receptor (AR) in hepatocarcinogenesis, but the underlying molecular mechanism remains unclear. Here, we used genome-wide location and functional analyses to identify a critical mediator of AR signaling — cell cycle–related kinase (CCRK) — that drives hepatocarcinogenesis via a signaling pathway dependent on β-catenin and T cell factor (TCF). Ligand-bound AR activated CCRK transcription and protein expression via direct binding to the androgen-responsive element of the CCRK promoter in human HCC cell lines. In vitro analyses showed that CCRK was critical in human cell lines for AR-induced cell cycle progression, hepatocellular proliferation, and malignant transformation. Ectopic expression of CCRK in immortalized human liver cells activated β-catenin/TCF signaling to stimulate cell cycle progression and to induce tumor formation, as shown in both xenograft and orthotopic models. Conversely, knockdown of CCRK decreased HCC cell growth, and this could be rescued by constitutively active β-catenin or TCF. In primary human HCC tissue samples, AR, CCRK, and β-catenin were concordantly overexpressed in the tumor cells. Furthermore, CCRK overexpression correlated with the tumor staging and poor overall survival of patients. Our results reveal a direct AR transcriptional target, CCRK, that promotes hepatocarcinogenesis through the upregulation of β-catenin/TCF signaling.